Unified control scheme for a dual-stage grid-connected PV system with mode change. (June 2022) - Wang, Yeqin; Ren, Beibei; Liyanage, Sanka
Abstract: This paper proposes a unified control scheme for a dual-stage grid-connected PV system to achieve both the maximum power point tracking (MPPT) mode and the droop mode of operation with mode change. The DC-bus voltage regulation is achieved through the DC–DC converter control, and different modes of operation and the MPPT function are implemented in the DC–AC converter control, where three digital switches are designed to achieve seamless mode change. To enhance system stability and flexibility, a droop coefficient self-tuning algorithm is proposed to handle the scenario with insufficient solar irradiation in the droop mode. The effectiveness of the proposed methods is validated through both experimental and simulation studies. Highlights: A unified control scheme is proposed for PV system to achieve seamless mode change. Seamless mode change is achieved with preserving the continuity of control signals. The decoupled control of both DC–DC converter and DC–AC converter is achieved. A droop coefficient self-tuning algorithm is proposed to avoid the instability issue. The proposed designs are experimentally validated on a PV-battery microgrid testbed.